2008
DOI: 10.1038/nature06808
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila pheromone cVA activates a sexually dimorphic neural circuit

Abstract: Courtship is an innate sexually dimorphic behaviour that can be observed in naive animals without previous learning or experience, suggesting that the neural circuits that mediate this behaviour are developmentally programmed. In Drosophila, courtship involves a complex yet stereotyped array of dimorphic behaviours that are regulated by Fru(M), a male-specific isoform of the fruitless gene. Fru(M) is expressed in about 2,000 neurons in the fly brain, including three subpopulations of olfactory sensory neurons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
314
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(323 citation statements)
references
References 26 publications
6
314
2
1
Order By: Relevance
“…The primary targets of PNs in the protocerebrum are calyces of the 6 mushroom body and/or part of the lateral protocerebrum, also known as the lateral horn (Fig. 3a) [3,9]. The PNs were classified as either uniglomerular PNs which spread dendrites to a single glomerulus (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary targets of PNs in the protocerebrum are calyces of the 6 mushroom body and/or part of the lateral protocerebrum, also known as the lateral horn (Fig. 3a) [3,9]. The PNs were classified as either uniglomerular PNs which spread dendrites to a single glomerulus (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…3), suggesting that the male-specific pathways could be formed by modification of the pre-existing, female-like pathways, analogous to the development of sexually dimorphic antennal sensilla. As it is presumed that integration of sensory signals and their conversion to behavioral decisions occurs in the neural pathway involving the lateral horn [3] this morphologic change must be preparatory to initiation of pheromone-triggered orientation behavior in adult males to adult females [5].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Or67d, the primary neuron of the DA1 olfactory circuit, detects Drosophila male-specific pheromone 11 cis-vaccenyl acetate (cVA) and triggers sex-specific courtship behavior in both male and female flies (Kurtovic et al 2007). In addition, the DA1 PNs show sexually dimorphic neural circuitry (Datta et al 2008). The primary neuron of DL3 (Or65a) also responds to cVA when flies are exposed to it for a long period.…”
Section: Glomerular Boundary Formation By Eph/ephrin For the Pheromonmentioning
confidence: 99%
“…It is surprising to find that a change in receptors for Z11-16:OAc could be responsible for the switch between the positive behavioral response of Hs and the negative response of Hv to this compound. In Drosophila where cis-vaccenyl acetate is attractive to females but repulsive to males, it is a central nervous system difference that controls the switch between positive and negative response (22). Furthermore, previous work showed that acetate responsive receptor neurons of Hv converge on a different glomerulus of the male macroglomerular complex compared to those of Hs (51).…”
mentioning
confidence: 99%
“…We now know that peripheral reception of pheromones involves a number of proteins in male antennae, including pheromone binding proteins (PBP), general odorant binding proteins (GOBP), chemosensory proteins (CSP), two classes of odorant receptors (OR), pheromone degrading enzymes (PDE), and sensory neuron membrane proteins (SNMP) (19)(20)(21). Genetic changes in the structure/expression of any or all of these proteins could have been involved in evolutionary diversification of moth sexual communication systems, but it is also possible that the crucial changes were in the male moth central nervous system (5,22).…”
mentioning
confidence: 99%